Results of the experimental study of the antimicrobial activity of therapeutic waters from various wells managed by the federation of trade unions of Uzbekistan - Shuhnaza T. Iskandarova; Zokhid A. Abdurakhimov; Dilnoza M. Musaeva (Вестник восстановительной медицины)
Introduction. Currently, in addition to the traditional use of mineral waters (MW) for the treatment of gastrointestinal tract and renal diseases, they are also used to correct metabolic disorders, normalize lipid and carbohydrate metabolism. However, many of its properties remain poorly studied, and there is a very limited number of works in the scientific literature concerning the analysis of their antibacterial action.